1979
DOI: 10.1128/iai.24.3.948-952.1979
|View full text |Cite
|
Sign up to set email alerts
|

Experimental bacterial keratitis in neutropenic guinea pigs: polymorphonuclear leukocytes in corneal host defense

Abstract: Quantitative techniques were used to determine the relative concentrations of viable bacteria and polymorphonuclear leukocytes (PMNs) in the corneas of neutropenic and non-neutropenic guinea pigs with experimental bacterial keratitis induced with three strains of Pseudomonas aeruginosa. Neutropenia was produced by whole-body X-irradiation 1 week before infection. Significantly greater numbers of bacteria were present in the corneas of neutropenic animals 48 h after infection than were present in the corneas of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 10 publications
(16 reference statements)
0
14
0
Order By: Relevance
“…4 Various studies indicate that the stimulated host responses may be more responsible for the further tissue damage than the invading pathogens. [2][3][4][5] Pseudomonas aeruginosa ocular clinical isolates exhibit three phenotypes: 6 (i) an invasive P. aeruginosa, which can invade epithelial cells; 7 (ii) a cytotoxic P. aeruginosa, which can cause epithelial cell cytotoxicity; 8 and (iii) a type of P. aeruginosa associated with contact lens induced acute red eye (CLARE) reaction. 9 The third type is neither cytotoxic nor invasive toward human corneal epithelial cells, 10 but can adhere to contact lenses.…”
Section: Introductionmentioning
confidence: 99%
“…4 Various studies indicate that the stimulated host responses may be more responsible for the further tissue damage than the invading pathogens. [2][3][4][5] Pseudomonas aeruginosa ocular clinical isolates exhibit three phenotypes: 6 (i) an invasive P. aeruginosa, which can invade epithelial cells; 7 (ii) a cytotoxic P. aeruginosa, which can cause epithelial cell cytotoxicity; 8 and (iii) a type of P. aeruginosa associated with contact lens induced acute red eye (CLARE) reaction. 9 The third type is neither cytotoxic nor invasive toward human corneal epithelial cells, 10 but can adhere to contact lenses.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that ocular IgA was made locally, whereas most ocular IgG may have originated from the serum, with some possible local synthesis. These immunological results indicate that DBA/2 and C57BL/6 mice respond differently to corneal challenge with P. aeruginosa.Pseudomonas aeruginosa is an opportunistic pathogen which causes severe corneal infections in humans and experimental animals (3,6,11,32,33). Previous experimental studies from our laboratory have indicated that DBA/2 mice can spontaneously restore corneal clarity within a few weeks after infection; they are therefore classified as naturally resistant (2, 12).…”
mentioning
confidence: 99%
“…Pseudomonas aeruginosa is an opportunistic pathogen which causes severe corneal infections in humans and experimental animals (3,6,11,32,33). Previous experimental studies from our laboratory have indicated that DBA/2 mice can spontaneously restore corneal clarity within a few weeks after infection; they are therefore classified as naturally resistant (2,12).…”
mentioning
confidence: 99%
“…The kinetics of the humoral response in susceptible C57BL/6J mice-were similar to those in resistant DBA/2J mice, although the magnitude of the response varied according to the antigen tested. These results indicate that LPS, exotoxin A, PLC, and flagella are present or produced in amounts that are immunogenic during corneal infection by P. aeruginosa 19660 in the mouse strains tested.Pseudomonas aeruginosa is an opportunistic pathogen which causes severe corneal infections in humans and experimental animals (6,8,14,37,38). The infection is usually preceded by corneal trauma.…”
mentioning
confidence: 99%
“…Pseudomonas aeruginosa is an opportunistic pathogen which causes severe corneal infections in humans and experimental animals (6,8,14,37,38). The infection is usually preceded by corneal trauma.…”
mentioning
confidence: 99%